Voting Beyond Borders: Evaluating UOCAVA’s Treatment of U.S. Territories and Overseas Citizens - Macy Cecil (Washington University Global Studies Law Review, 2024)
The Uniformed and Overseas Citizens Absentee Voting Act (UOCAVA) enfranchises millions of U.S. citizens living abroad, enabling their participation in federal elections. However, by defining “United States” to include only certain territories—namely, American Samoa, Guam, Puerto Rico, and the U.S. Virgin Islands—UOCAVA excludes their residents from qualifying as overseas voters. In contrast, former state residents who move to the Commonwealth of the Northern Mariana Islands or a foreign country retain the ability to vote absentee in federal elections in their former state. As a result, former state residents hold different federal voting power depending on where they relocate. This arbitrary enfranchisement raises constitutional and international concerns, including violations of the Equal Protection Clause, the right to travel, and the principle of equal suffrage under international treaties. This note critiques UOCAVA’s inconsistent treatment of select U.S. territories by assessing its compliance with the Constitution and international norms, and it proposes legislative reforms to address these inequities. These proposals include removing the territories from UOCAVA’s definition provisions or granting the territories full voting rights through constitutional amendment. By rectifying these disparities, the United States can better fulfill its constitutional and international obligations while fostering a more inclusive electorate.
Keywords: UOCAVA; uniformed and overseas citizens absentee voting act; federal; election; voters; vote; american; samoa; guam; Puerto rico; virgin islands; commonwealth; absentee; foreign; resident; constitutional; international; equal protection clause; treaties; treaty; inequity; inequities; electorate